Penguatan Pendidikan Karakter Disiplin dan Tanggung Jawab pada Siswa Sekolah Dasar melalui Kebiasaan, Pengalaman, dan Dukungan Lingkungan Sekolah - Zahra Nadyanda A; Ibnu Muthi (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine how habits, experiences, and school environmental support can strengthen character education of discipline and responsibility in elementary school students. Using a qualitative approach and literature study method, data were obtained from various academic sources such as scientific journals, reference books, and relevant research reports. The results of the analysis show that simple habits that are carried out repeatedly, such as arriving on time, following class duty, and obeying school rules, can instill a consistent attitude of discipline in students' lives. Meanwhile, real experiences gained by students through project activities, group work, and involvement in social activities contribute greatly to the understanding and appreciation of the value of responsibility contextually. Support from the school environment, including the role of teachers as role models, a conducive school culture, and facilities that support learning, are important factors that strengthen the process of internalizing character. These three aspects - habits, experiences, and environment - interact with each other and form a comprehensive character education system. In conclusion, effective character education in forming attitudes of discipline and responsibility is not enough to be theoretical, but must be built through consistent and collaborative concrete practices in the school environment.